GAN을 활용한 고품질 이미지 생성 플랫폼 - 가은성(Eunseong Ka); 김범기(Beomgi Kim); 이승철(Seungcheol Lee); 조현민(Hyunmin Cho); 조풍진(Poongjin Cho) (디지털콘텐츠학회논문지, 2023)
본 논문은 이미지 생성 딥러닝 기법인 RealSR, Waifu2X 그리고 Bringing Old Photos Back to Life와 클라우드 컴퓨팅을 통합하여접근성 및 확장성 높은 새로운 클라우드 기반 이미지 복원 서비스를 제안한다. 해당 서비스는 오래된 사진 복원, 저해상도 이미지개선 기능을 제공하며, 다양한 디지털 미디어 콘텐츠의 사례에 적용할 수 있다. 또한, 사용자 친화적인 플랫폼을 제공함으로써, 다양한 분야의 사용자들이 인공지능에 대한 지식 없이 딥러닝 이미지 생성 모델을 쉽게 이용할 수 있다. 클라우드 기반 아키텍처는확장성을 보장하며, 다양한 사용자의 요구를 처리하고 적응할 수 있게 한다. 본 논문에서는 딥러닝 이미지 생성 모델을 클라우드서비스로의 통합을 통해, 보다 넓은 대중에게 고품질 이미지 복원 기능에 접근할 수 있게 하고, 이는 디지털 콘텐츠 분야에 큰 영향을 끼칠 것으로 기대한다. This study proposes a novel cloud-based image restoration service that integrates advanced image generation deep learningtechniques such as RealSR, Waifu2X, and Bringing Old Photos Back to Life with cloud computing, which enhances accessibilityand scalability. The service provides features for restoring aged photographs and enhancing low-resolution images, and can beapplied to various cases of digital media content. By constructing a user-friendly platform, users from various fields can easilyutilize deep learning image generation models without extensive AI knowledge. The cloud-based architecture guarantees scalability,enabling the service to manage diverse user demands and adapt accordingly. This study illustrates how the integration of deeplearning image generation models into a cloud service enables broader accessibility to high-quality image restoration capabilitiesfor the general public. Moreover, it is anticipated that it can significantly impact the digital content industry. KCI Citation Count: 0